Development of a Volleyball Game Upper Passing Training Model - Dewi, Utami; Fuzita, Mira (JUPE : Jurnal Pendidikan Mandala, 2023)
Volleyball coaching includes various aspects involving players, coaches, training models and training programs needed to develop abilities and skills in volleyball. The aim of this research is a model of passing training in volleyball games. This research study uses 3 experts divided into several expert fields as lecturers who teach volleyball courses and volleyball coaches. Of the 15 top passing training models developed, only 12 training models were approved to be implemented and implemented. Recapitulation of the percentage of training models from expert lecturers was 80%, trainer 1 was 78% and trainer 2 was 75%. The research method used is research and development, research and development activities which aim to develop and create a more effective and efficient training model. It is hoped that this research can help the world of sports, especially volleyball in Indonesia, so that it can trigger the emergence of new ideas in developing other volleyball training models in the future.